Efektivitas dan Peran Guru Dalam Kurikulum Merdeka Belajar - Atin Sri Handayani; Kantri Nurlisa; Mustafiyanti Mustafiyanti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The effectiveness of learning is certainly an important issue, but if you look at the development in the world of education and also the role of teachers today is changing more and more so it is very important to consider the effectiveness and role of teachers in the independent learning curriculum. Teachers as free learners are needed as active and enthusiastic leaders, creative, innovative, and good at being helpers of change in schools. The purpose of writing this article is to discuss the effectiveness of learning and most importantly the role of the teacher itself, especially in the use of the independent learning curriculum as it is today. Then literature related to data sources used themes, be it books, articles, journals, and other sources on the internet. The research method of library research is used by finding and collecting relevant sources, with the tena studied or raised, then drawing conclusions and recording important things and then implemented in writing.